Proposta de modelo de gerenciamento de Propriedade Intelectual nos Núcleos de Inovação Tecnológica - NIT de Maceió/AL - Oliveira, Elton Henrique Alves de (2019)
Intellectual property (IP) plays an important role in both management and development plans of Universities. Hence, all the innovative creations whose are eligible for patent application or licensing are expected to be aligned to Research, Technology and Innovations policies. As a strategy, the management of IP must guarantee rights and also protection to the innovative creations since this measurement reinforces the innovative processes. However, the successful of the technological, economy, social and competitive development depends on the ability in to identify, to improve and to explore the creations potentially innovative in order to apply to the protective measures. These measures are possible when systems towards monitoring, evaluation and ranking are available. Thus, the proposal of this study is to present a management model for the treatment of the research developed at CESMAC and UNCISAL through the submission of Technological Readiness Level (TRL) forms, where, from the answers, it will be possible to evaluate and classify the potential the emergence of new technologies and thus carry out the appropriate procedures for protection through intellectual property rights and thus, consequently, exploit the benefits of such asset guaranteed by law.